efektivitas layanan informasi dengan topik bakat dan minat terhadap perencanaan karir siswa kelas XI IPS 1 Sma N 8 Surakarta Tahun Pelajaran 2022/2023 - Setyowati, anggun (Program Studi Bimbingan dan Konseling FKIP Universitas Slamet Riyadi, 2023)
Researchers have a goal to determine the effectiveness of information services on the topic of career planning, talents a,nd interests of students in class XI IPS 1 SMAN 8 Surakarta in the 2022/2023 academic year. The research conducted includes experimental quantitative research. Researchers used a student population of 36. Researchers used a sample of all students. Thus, the sampling method used is the saturated sampling method. Researchers used student questionnaire trials. The researcher used the questionnaire data method and documentation. The main method is a questionnaire and the assisting technique is documentation. The researcher when analyzing the data used the t-test equation. According to the results of the analysis obtained with the effectiveness of information services on the topic of talent and interest in student career planning, obtained t-countwas 14,396, after that the t-table was consulted with d.b=N-1(36-1), referring to the t-table with a significance level 1% = 2.724, significance level 5% = 2.030, while the arithmetic value is greater than the t-table (Implementation of Information Services with Topics of Talents and Interests is not effective in planning student careers) is not true, Ha who is accepted suggests the implementation of information services on the topic effective talent and interest in student career planning are true.